THE EFFECT OF LIVE STREAMING, RATINGS, AND PRODUCT REVIEWS ON PURCHASING DECISIONS FOR COMPASS SHOE PRODUCTS IN THE SHOPEE APPLICATION - M. Ivan Imanulloh Khaqi; Mochamad Rizal Yulianto; Andry Rachmadany (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the effect of the live streaming feature, product ratings, and product reviews on purchasing decisions for Compass shoes in the Shopee application. Method: Using multiple linear regression techniques, the study identified that all independent variables (live streaming, ratings, and product reviews) have a positive and significant relationship to purchasing decisions, and the research instrument proved to be reliable with Cronbach's Alpha and Composite Reliability values above 0.7 for all constructs. Results: The analysis results show that the product review variable (X3) has the most significant influence, while live streaming (X1) has the smallest influence, and the research model shows moderate predictive power of purchasing decisions (R Square=0.528). Novelty: This finding confirms the importance of reviews, ratings, and real-time interactions in encouraging consumers to make purchasing decisions in digital marketplaces.